Tanggung Jawab Hukum Over The Top News Aggregator Terhadap Pelanggaran Hak Ekonomi Produk Jurnalistik - Muhammad, Duta; Ramli, Tasya Safiranita; Permata, Rika Ratna (Media Hukum Indonesia (MHI), 2025)
The growth of Over The Top (OTT) services has made it more difficult to protect press companies' economic rights over their news content. OTT News Aggregators often distribute news without proper permission or fair compensation, leading to financial harm for news publishers. This situation raises legal concerns about the protection mechanisms and liability of OTT News Aggregators in Indonesia. This study uses a normative juridical approach, analyzing laws, legal doctrines, and scholarly opinions related to violations of economic rights by OTT platforms. According to this study, online news content is safeguarded by the Press Law, the Copyright Law, and the Electronic Information and Transactions Law (ITE Law). Presidential Regulation No. 32 of 2024 on Publisher Rights, specifically Articles 5(f) and 7, which mandate that digital platforms collaborate with press institutions, strengthens these safeguards. However, only the non-binding Circular Letter of the Minister of Communication and Informatics No. 3 of 2016 addresses the legal obligation of OTT News Aggregators, so leaving it weak. Therefore, there is a need to update the ITE Law, PP PSTE, and Ministerial Regulation No. 5 of 2020, and to introduce strict liability to ensure better accountability and protection of economic rights.